Dietary antioxidants supplementation increases sperm motility, fertility and oxidative enzyme activity during milt cryopreservation of koi carp Cyprinus carpio Linnaeus, 1758 - Betsy, Judith; S, Sangavi; M, Saravanan (Indian Journal of Fisheries, 2026)
In aquaculture, oxidative stress is considered a major problem as it impairs sperm motility and cell viability, especially during cryopreservation. This can be overcome by dietary supplementation of antioxidants, which is essential during gametogenesis and spermiation. Hence, the present study aimed at evaluating the influence of dietary antioxidants on sperm quality and oxidative enzyme activity during cryopreservation. Experimental fishes (Cyprinus carpio L.) were fed with feed supplemented with vitamin C and E at three different concentrations, which consisted of 6 treatments and a control (without vitamin inclusion). The experimental feed was fed to the fish until satiation for 60 days, after which, milt was collected from the fish and cryopreserved for 30 days. After 30 days of cryopreservation, fertilisation was done using cryopreserved milt and fresh milt. The oxidative enzyme activity, such as glutathione peroxidase, catalase and superoxide dismutase, was recorded. The values of motility duration, fertilisation and hatching rate showed an overall linear and quadratic significant differences (p<0.05) among the treatments. The histological analysis of the ovary was also documented to analyse the effect of antioxidants on the ovarian development. Feed supplemented with vitamin E at 200 mg kg-1 (T4) exhibited higher motility value, fertilisation and hatching rates and oxidative enzyme activities in comparison to other treatments. Keywords: Fertilisation, Gametogenesis, Hatching rate, Histology, Spermiation